Construction of Complete (k,n)-arcs in the Projective Plane PG(2,11) Over Galois Field GF(11), 3 ï‚£ n ï‚£ 11 - Mahammad, A.T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this work is to construct complete (k,n)-arcs in the projective 2-space PG(2,q) over Galois field GF(11) by adding some points of index zero to complete (k,nâ€“1)arcs 3 ï‚£ n ï‚£ 11.         A (k,n)-arcs is a set of k points no n + 1 of which are collinear.         A (k,n)-arcs is complete if it is not contained in a (k + 1,n)-arc